EFFORTS TO IMPROVE THE SHOW AND TELL METHOD ON SPEAKING SKILLS IN CLASS V STUDENTS - Ahmed, Mohammedalameen; Darmayanti, Rani; Usmiyatun, Usmiyatun; Aini, Nur; Choirudin, Choirudin; Karim, Samuel (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2023)
StudyThis aims to: 1) improve speaking skills through learning activities and 2) improve speaking skills using the show-and-tell method for fifth-grade students at SD Negeri 12 Selat Penuguan. This type of research is classroom action research. The subjects in this research were class V students at SD Negeri 12 Penuguan Strait for the 2022/2023 academic year, totaling 32 students. The research design refers to classroom action research according to Kemmis which includes 1) planning 2) action implementation 3) observation and 4) reflection. The data collection methods used in this method are: 1) test 2) observation 3) documentation. Descriptive statistical data analysis techniques were used to analyze quantitative data, namely the average value, while the flow model was used for qualitative data analysis. The research results show that the use of the storytelling method can improve learning activities and speaking skills through the show and tell method. This is characterized by increased speaking skills in the aspects of pronunciation, intonation, word choice, sequence, courage, fluency, attitude, and mastery of themes